Effects of loaded and unloaded jumps used as priming activities in elite male rugby union players - Loturco, I.; Zmijewski, P.; Mercer, V. P.; Moura, T. B. M. A.; Ramos, M. S.; Betelli, M. T.; Pereira, L. A.; McGuigan, M. R. (The Journal of Strength and Conditioning Research, 2025)
This randomized crossover study examined the effects of 2 distinct priming activities on strength, speed, and power performance of elite rugby players. Twenty male rugby union players from the Brazilian National Team were tested on 3 occasions, 1 week apart, during the final phase of preparation for the "American Rugby Super League." In the first session (baseline), players performed tests for countermovement jump (CMJ), drop jump (DJ), loaded jump squat (JS), sprint speed, and maximum isometric force (MIF) in the half squat (HS). In addition, to determine the loads for the priming exercises (i.e., JS and DJ), the DJ height associated with the best reactive strength index (RSI) and the 1RM in the HS were also assessed. In the following 2 weeks, both experimental protocols were implemented. After a standardized warm-up, players completed the priming activities in a randomized order, consisting of 6 × 6 DJs from the height yielding the best RSI or 6 sets of JS at 40% HS-1RM. After this, at 6-hour and 24-hour postpriming sessions, they were tested for jumping and sprinting abilities, peak velocity in the JS, and MIF in the HS. Our results showed that both exercises were effective in improving performance at different time intervals, with the JS demonstrating clear superiority over the DJ. Jump-squat peak velocity at 30 and 100% of body mass increased significantly at both time intervals across both exercises, whereas CMJ height increased only at the 6-hour testing session after the JS protocol. Sprinting speed improved significantly only after JSs, highlighting the effectiveness of this ballistic exercise in enhancing the speed performance of team-sport athletes. Coaches are encouraged to prescribe jumping exercises, especially with light loads, in periods preceding matches and competitions.